Analisis Pengaruh Kompetensi Terhadap Kinerja Karyawan Badan Pengelola Dan Pengembangan Taman Mini Indonesia Indah - Zakiyah, Zakiyah; Ariyanto, Eny (Akmenika, 2016)
Taman Mini Indonesia Indah (TMII) is the second largest tourist destination inJakarta. Until now TMII is managed by the Management Board and DevelopmentTaman Mini Indonesia Indah (TMII BPP). The number of employees BPP TMII,early out by 2015, as many as 734 people. In the period 2011-2014, employeesperformance BPP TMII yet optimal and showed the phenomenon tends to decrease.Similarly, the level of competency of the employees pointed to the fact remains lowordo not meet minimum standards set BPP TMII management, among others, by78.75% of the employees had high school education or less. The issue is whether theemployees competence affect the performance? with reference to the formulation ofthe problem, the study aims to examine and analyze whether BPP TMII employeescompetence variable effect on performance. The study design used is associativeresearch. The study population was all employees assigned BPP TMII. Because ofthe size of the population is large, this study used a sample. The minimum samplesize is determined by the formula Slovin and with a level of fault tolerance selectedby 5%, then obtained a sample size of 259 people. The sampling method used simplerandom sampling. Furthermore, the research hypothesis was tested using statisticalmodels of linear regression and multiple linear regression. The test results prove thehypothesis that the variables of competence by dimensional motif, character, selfconfidence,knowledge, skills, either partially or simultaneously have a significantpositive effect on employees performance BPP TMII, and the coefficient ofdetermination obtained 52.7%.